2020
DOI: 10.1007/s12070-020-02201-4
|View full text |Cite
|
Sign up to set email alerts
|

‘POLIDON’ Approach—A Novel Solution for the ENT & Skull Base Surgeons in COVID-19 era

Abstract: Health care providers (HCP) of ENT and Skull base surgery are highly vulnerable and mostly infected by novel coronavirus as they have to examine and perform procedures directly in oral cavity, oropharynx, nose, nasopharynx, where coronavirus remains in plenty. ENT & Skull base surgeons need to do several aerosol generating procedures (AGP). Most of the endoscopic and microscopic ENT & skull base surgery are AGP; like-mastoid surgery, sinus surgery, surgery of pituitary, tympanomastoid paraganglioma, temporal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Arefin et al 28 reported a new approach combining polyethylene protection fields with PVP-Ibased mouthwashes. According to the authors, both health professionals and patients should perform preoperative mouthwashes with 10 mL of 1% PVP-I solution, for 1 minute.…”
Section: Resultsmentioning
confidence: 99%
“…Arefin et al 28 reported a new approach combining polyethylene protection fields with PVP-Ibased mouthwashes. According to the authors, both health professionals and patients should perform preoperative mouthwashes with 10 mL of 1% PVP-I solution, for 1 minute.…”
Section: Resultsmentioning
confidence: 99%
“…Since May 2020 I have attended more than 7000 patient in OPD and emergency, performed 501 endoscopy of larynx and nose (FOL, DNE) and 203 surgeries, including tracheostomy, mastoidectomy, endoscopic sinus surgery, skull base surgery, laryngeal biopsy, tonsillectomy, septoplasty etc. These are airway surgeries and moreover, most of them are aerosol generating procedures) [ 12 , 13 , 14 ].…”
Section: My Experience With Pvp-i In Covid-19 Eramentioning
confidence: 99%
“…Interestingly, among twelve different health care providers, including doctors, nurses and OT staffs, directly involved and exposed in these two surgeries, none of them were infected. Importantly, ‘POLIDON’ approach was followed in both the procedures [ 12 , 14 ].…”
Section: My Experience With Pvp-i In Covid-19 Eramentioning
confidence: 99%
“…Five very similar feasibility studies report on their experience of specific patient draping. [29][30][31][32][33] The majority employ a polythene sheet, under which the surgeon operates. [29][30][31][32] Of these, only Arefin et al (2021) 29 published outcomes, reporting no COVID-19 infections amongst twelve theatre team members over a fivemonth period.…”
Section: Adjunctive Techniquesmentioning
confidence: 99%
“…[29][30][31][32][33] The majority employ a polythene sheet, under which the surgeon operates. [29][30][31][32] Of these, only Arefin et al (2021) 29 published outcomes, reporting no COVID-19 infections amongst twelve theatre team members over a fivemonth period. Both Ioannidis et al (2020) 34 and David et al (2020) 35 also draped the patient in a polythlene sheet but, in a similar strategy to Jones et al (2020) 16 above, attached suction to create a negative pressure environment.…”
Section: Adjunctive Techniquesmentioning
confidence: 99%